2015
DOI: 10.1039/c5ra05620a
|View full text |Cite
|
Sign up to set email alerts
|

Aggregated Pt–Pd nanoparticles on Nafion membrane for impulsive decomposition of hydrogen peroxide

Abstract: A Pd site initiates hydrogen peroxide decomposition by adsorbing one ‘O’ followed by splitting of O–H bond. Meanwhile, a Pt site finally completes the decomposition process by enabling desorption of the incipient O2 species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Several studies have reported the lowering of the ɛ d value of Pt to a moderate value upon incorporation of Pd in the Pt catalyst . Our experimental observations for the NNR rate enhancement using binary and ternary catalyst assemblies indicate that moderate ɛ d values are obtained for the catalytic assemblies molded with equal amounts of Pt and Pd (Pt/Pd ratio ≈1).…”
Section: Resultsmentioning
confidence: 49%
“…Several studies have reported the lowering of the ɛ d value of Pt to a moderate value upon incorporation of Pd in the Pt catalyst . Our experimental observations for the NNR rate enhancement using binary and ternary catalyst assemblies indicate that moderate ɛ d values are obtained for the catalytic assemblies molded with equal amounts of Pt and Pd (Pt/Pd ratio ≈1).…”
Section: Resultsmentioning
confidence: 49%
“…2,3 For example, aggregated Pt-Pd nanoparticles on Nafion membrane was reported for impulsive decomposition of H 2 O 2 . 4 Li 5 employed carbon-doping molybdenum carbide (β-Mo 2 C/C) to modify glassy carbon electrode, and the synergistic effect of β-Mo 2 C/C made the sensor show outstanding electrocatalytic performances toward H 2 O 2 . Ahammad 6 fabricated palladium thin film on indium tin oxide electrode for electrochemical detection of H 2 O 2 and proposed a possible reduction reaction mechanism.…”
mentioning
confidence: 99%